Urbanization and prevalence of type 2 diabetes in Southern Asia: a systematic analysis - Arsalan Cheema; Davies Adeloye; Simrita Sidhu; Devi Sridhar; Kit Yee Chan (Edinburgh University Global Health Society, 2014)
Diabetes mellitus is one of the diseases considered to be the main constituents of the global non-communicable disease (NCD) pandemic. Despite the large impact that NCDs are predicted to have, particularly in developing countries, estimates of disease burden are sparse and inconsistent. This systematic review transparently estimates prevalence of type 2 diabetes mellitus in Southern Asia, its association with urbanization and provides insight into the policy challenges facing the region.